2018
DOI: 10.1007/s10815-018-1371-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-ovarian injection of mesenchymal stem cells in aged mares

Abstract: Purpose This study aims to determine if intra-ovarian injection of bone marrow-derived mesenchymal stem cells (MSCs) improves or restores ovarian function in aged females. Methods Prospective randomized study of eight aged mares and six young mares receiving intra-ovarian injection of MSCs or vehicle. Main outcome measures were antral follicle count and serum anti-Müllerian hormone (AMH) (aged and young mares), and for aged mares, oocyte meiotic and developmental competence; gross and histological ovarian asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…There are multiple sources of multipotent stem cells in both adults and fetuses. Some are autologous, meaning that they can be transplanted into the donor, and some are allogeneic, meaning that they can be transplanted into patients other than the donor [23]. Stem cells that can be isolated from adults include BMMSCs, adipose-derived mesenchymal stem cells (ADSCs) and peripheral blood mononuclear cells (PBMCs).…”
Section: Sources Of Stem Cellsmentioning
confidence: 99%
“…There are multiple sources of multipotent stem cells in both adults and fetuses. Some are autologous, meaning that they can be transplanted into the donor, and some are allogeneic, meaning that they can be transplanted into patients other than the donor [23]. Stem cells that can be isolated from adults include BMMSCs, adipose-derived mesenchymal stem cells (ADSCs) and peripheral blood mononuclear cells (PBMCs).…”
Section: Sources Of Stem Cellsmentioning
confidence: 99%
“…Stem-cell therapy has been shown to improve ovarian function in laboratory animal models in which infertility was artificially induced [25][26][27][28][29] . However, the clinical use in large farm animals is still under discussion 30,31 . The present study was designed to evaluate the effect of intraovarian MSC treatment on oocyte yield and embryo production.…”
mentioning
confidence: 99%
“…Prior research has shown similar improvements in ovarian function with stem cells from other lineages including tissue sources as diverse as bone marrow, 8,9,[26][27][28] amniotic epithelium, 10 amniotic fluid, 11 human menstrual blood stem cells, 29 MSCs, [30][31][32] and adipose tissue. 33 The biological mechanism of this improvement has been a topic of discussion for some time.…”
Section: Discussionmentioning
confidence: 94%